Enquiring into the contributions of African philosophic conceptualisations of human rights to the modern disource of human rights - Kante, Babacar (University of Pretoria, 2011)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2010.